Propofol infusions using a human target controlled infusion (TCI) pump in chimpanzees (Pan troglodytes) - T. Miyabe-Nishiwaki (Nature Portfolio, 2021)
Abstract Chimpanzees are genetically and physiologically similar to humans. Several pharmacokinetic models of propofol are available and target controlled infusion (TCI) of propofol is established in humans, but not in chimpanzees. The purpose of this study was to investigate if human pharmacokinetic models can accurately predict propofol plasma concentration (Cp) in chimpanzees and if it is feasible to perform TCI in chimpanzees. Ten chimpanzees were anaesthetized for regular veterinary examinations. Propofol was used as an induction or maintenance agent. Blood samples were collected from a catheter in a cephalic vein at 3–7 time points between 1 and 100 min following the propofol bolus and/or infusion in five chimpanzees, or TCI in six chimpanzees. Cp was measured using high-performance liquid chromatography. The Marsh, Schnider and Eleveld human pharmacokinetic models were used to predict Cp for each case and we examined the predictive performances of these models using the Varvel criteria Median PE and Median APE. Median PE and Median APE for Marsh, Schnider and Eleveld models were within or close to the acceptable range. A human TCI pump was successfully maintained propofol Cp during general anesthesia in six chimpanzees. Human propofol pharmacokinetic models and TCI pumps can be applied in chimpanzees.